Mental Disorders in Children and Adolescents in Crisis Situations: The Impact of the COVID-19 Pandemic and Armed Conflicts - Types of Disorders, Effects, and Intervention Strategies - Gadżała, Katarzyna; Przygodzka, Sabina; Rutkiewicz, Maciej; Garbino, Karolina; Brudniak, Katarzyna; Szuścik , Antoni; Czyczerska, Magdalena (Quality in Sport, 2025)
Introduction. The deterioration of mental health in children and adolescents is a serious medical problem, and the number of mental disorders has been increasing in recent years. In every part of the world, children and adolescents suffer from mental health problems, and their needs are not adequately taken care of. In addition, the outbreak of the COVID-19 pandemic and armed conflicts have had a significant impact on the emergence of disorders in children and adolescents. Loneliness, fear, anxiety and lack of emotional support and access to appropriate medical and psychological care are the basis of these problems. Support for young patients, psychological and pharmacological interventions and raising awareness about the importance of mental health are the basis for improving the mental health of adolescents. Aim of study. The aim of this study is to investigate the increasing prevalence of mental disorders among children and adolescents and to examine their correlation with the occurrence of pandemics, wars and traumas. Materials and methods. A non-systematic review of the scientific literature was conducted using specific keywords such as “children’s mental health”, “youth mental health”, “COVID-19 pandemic”, “war in Ukraine”, “armed conflicts”, “mental disorders”, “depression” and “anxiety”. The review was conducted in the Pub Med database, analyzing a total of 39 sources published by the end of 2024. Conclusions. Both the COVID-19 pandemic and armed conflicts have a negative impact on the mental health of children and adolescents worldwide. The occurrence of previous mental health problems significantly increases the risk of anxiety disorders, PTSD, depression. The basic strategy for preventing the occurrence and reducing the severity of these disorders are preventive programs, psychoeducation, psychotherapy, if necessary combined with pharmacotherapy.